Past, present, and future of the technological tracking methods to assess tactical variables in team sports: A systematic review - Rico-González, M.; Pino-Ortega, J.; Nakamura, F. Y.; Arruda Moura, F.; Rojas-Valverde, D.; Los Arcos, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
The main aim of this work was to review the use of technological tracking methods to assess collective spatial-positioning variables in team sports. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and PICO design for systematic reviews, study identification was performed in four databases (PubMed, SPORTDiscus, ProQuest Central, and Web of Science). Articles were selected if they focused on player position and technological tracking methods. After duplicate removal, 2194 articles were identified based on the established search criteria, of which 72 articles were selected and analysed. Semi-automatic optic-based systems, Global Positioning System/Global Navigation Satellite Systems, and local positioning systems were used in 60%, 33% and 7% of the studies, respectively. All studies that measured tactical variables by local positioning system technology in team sports used local position measurement technology. Optic-based systems were used more often in the early years to analyse collective tactical behaviour during competition. Later, Global Positioning System/Global Navigation Satellite Systems became more frequent to measure behaviour in team sports during the training process. The possibility of using the same system during competition and training will facilitate the assessment of collective tactical behaviour in team sports.